2016
DOI: 10.1109/tgrs.2015.2501372
|View full text |Cite
|
Sign up to set email alerts
|

Optimum Surface Roughness to Parameterize Advanced Integral Equation Model for Soil Moisture Retrieval in Prairie Area Using Radarsat-2 Data

Abstract: The distribution of soil moisture is important for modeling hydrological and climatological processes to understand the Earth energy cycle and balance. The major difficulty for soil moisture retrieval in vegetated areas is how to separate the individual scattering contribution of soil moisture, vegetation, and surface roughness from the backscattered radar signal. In this paper, a semi-empirical method was proposed to retrieve soil moisture in the Ruoergai prairie using single temporal Radarsat-2 data. It was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
43
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(45 citation statements)
references
References 58 publications
2
43
0
Order By: Relevance
“…From the contours, it is observed that the impact of an increase in s can be balanced by an increase in l, and there may exist multiple solutions for the effective roughness parameters. These two phenomena have also been observed in the work of Bai et al [33], which were caused by an ill-posed AIEM.…”
Section: Calibration For the Coupled Modelsupporting
confidence: 65%
See 3 more Smart Citations
“…From the contours, it is observed that the impact of an increase in s can be balanced by an increase in l, and there may exist multiple solutions for the effective roughness parameters. These two phenomena have also been observed in the work of Bai et al [33], which were caused by an ill-posed AIEM.…”
Section: Calibration For the Coupled Modelsupporting
confidence: 65%
“…The s and l are parameterized based on the effective roughness parameters, which have been used in previous studies [30] (pp. 178-180), [33] (pp. 2440-2441), and [53] (pp.…”
Section: Bare Soil Backscattering Modellingmentioning
confidence: 99%
See 2 more Smart Citations
“…2017, 9, 580 2 of 14 the sensor type and length of the rods, the measurement depth usually varies between 5 cm and 15 cm. Most studies ignore the problems of mismatching measuring depths and utilize this kind of in situ data from low frequency L-band [1][2][3] to high frequency C- [4][5][6] and even X-band SAR data [7][8][9]. While the obtained information is generally not fully suitable for high frequency SAR data due to the limited penetration into the soil, in some cases it might also be misleading for L-band data when the soil is dry and the penetration depth exceeds the sensor depth.…”
Section: Introductionmentioning
confidence: 99%